RS15-LC62 Diatom counts and biogenic silica from Moubray Bay, northwest Ross Sea, Antarctica - Greer Gilmer; Christina R Riesselman; Sunghan Kim (PANGAEA, 2025)
A high-resolution record of diatom counts and biogenic silica in sediment core RS15-LC62 collected from Moubray Bay, northwest Ross Sea, Antarctica by Korea Polar Research Institute (KOPRI) expedition ANA05B in 2015. Core is 4.8 m long. Sediment samples were collected from lamination pairs or triplets in the upper ~2.3 m of the core and then as 1 cm thick sediment samples below 2.3 m due to textural differences in the core. Data includes diatom census counts, relative diatom abundance (RDA) of the three most dominant taxa downcore, absolute diatom abundance (ADA), and wt% biogenic silica. Data was used to reconstruct changes in environmental conditions such as sea ice concentration and water column structure over ~500 years during the early Holocene.